FENOMENA GADAI LAHAN SAWAH DI KOTA PADANGSIDIMPUAN - Dalimunthe, Dermina (Yurisprudentia: Jurnal Hukum Ekonomi, 2024)
Sometimes, individuals encounter financial difficulties in covering all their needs. In this regard, Islam advises its followers to extend a helping hand to those in need, manifested through acts such as grants and loans. Pawn agreements present an alternative solution for communities; however, the ironic reality is that pawn practices found in society often involve usury, which is prohibited by Islamic law. In the realm of Islamic commercial jurisprudence (Fiqh muamalah), a pawn agreement is referred to as "rahn." Rahn involves pledging an item as collateral for a debt transaction. Due to its nature as a "tabaru'" contract, it prohibits any benefit to be gained by the pledger (murtahin). Nevertheless, the murtahin is allowed to collect maintenance fees from the pledger if the pawned item requires maintenance. The significance of pawning in Islam lies in its social function, aiming to assist fellow members of the community. The phenomenon of pawning agricultural land in Padangsidimpuan City, both in terms of conditions and pillars, is not yet valid from a utilization perspective as it still involves usury. Person terkadang bertemu kesusahan finansial untuk menutupi seluruh keperluanya, untuk itu agama Islam sudah memberitahukan agar penganutnya selalu mengulurkan tangan kepada yang membutuhkan, wujudnya dapat berupa hibah dan utang. Perjanjian gadai adalah alternatif solusi bagi masyarakat, ironisnya praktik gadai yang dijumpai dalam masyarakat masih mengandung riba yang diharamkan oleh hukum Islam. Dalam Fiqh muamalah perjanjian gadai disebut rahn. Rahn adalah menggadaikan suatu barang sebagai jaminan atas transaksi utang. Disebabkan sifatnya adalah akad tabaru’, maka dilarang ada manfaat yang diambil oleh murtahin. Murtahin boleh memungut biaya perawatan dari rahin jika benda gadai membutuhkan perawatan. Urgensi gadai dalam Islam adalah hubungan sosial guna membantu sesamanya. Fenomena gadai lahan sawah di Kota Padangsidimpuan dari sisi syarat dan rukun secara total belum sah dari sisi pemanfaatan masih mengandung riba.